CADMIUM TOXICITY ON BIOCHEMICAL CONSTITUENTS IN THE LIVER OF FRESH WATER FISH CYPRINUS CARPIO (LINN). - A. PARITHA BHANU; M.DEEPAK (International Journal of Pharma and Bio Sciences, 2015)
Static bioassays were carried out to find LC50 96hr value of cadmium to the fresh water fish. Cyprinus carpio. It was found to be 1.0 % .After the determination of LC50 96hr values, groups of 10 fishes were exposed to different sublethal concentrations of the metal for 30days to evaluate chronic toxicity. Liver was used to determine various biochemical constitutions such as total carbohydrates, total proteins and total lipids. All the biochemical parameters were found to decrease in the experimental fishes in dose and duration dependent manner. The fall in the level of biochemical parameters in the liver of fishes could be attributed to the production of extra energy to cope up with the toxic stress caused by cadmium.